Dividend changes and catering incentives - Li, Wei; Lie, Erik (Journal of Financial Economics, 2006)
We extend Baker and Wurgler's [2004a. Journal of Finance 59 1125–1165] catering theory to include decreases and increases in existing dividends. Consistent with our extended model, we find that the decision to change the dividend and the magnitude of the change depend on the premium that the capital market places on dividends. We also find that the stock market reaction to dividend changes depends on the dividend premium. Thus, the capital market rewards managers for considering investor demand for dividends when making decisions about the level of dividends.